‘One man’s meat is another man’s poison’. The Rhetoric of Dissent in John Henry Cardinal Newman’s Apologia pro Vita Sua (1864) - Bertrand Lentsch (Cahiers Victoriens et Edouardiens)
John Henry Newman has been blamed for being highly strung. A man who would make amends, to atone for a lambasted decision to abide by a rule, which he now deemed honourable though he then branded it as dishonest, could only be expected to keep his secrets secret. His thereafter feeling impelled to deliver Apologia pro Vita Sua, to rebut the charge of deluding himself and beguiling the throng of well-wishers, raised eyebrows. The diary of his conversion is yet no anticlimax, since he wilfully enshrined his apology in apologetics. A proud British, and an Oxbridge divine, with a lifelong pledge to make out the truth in the maze of a schism, needs must when the devil drives. His counterevidence stemmed from his pious assent that his detractor’s doubt was not devoid of acumen, so his asseveration was redolent of his indebtedness to forefathers, whose authority he made it a point of honour of ascertaining. That self-styled self-assertion has hence a ring of truth, for making much ado about nothing, as befits truth, which is stranger than fiction. A return to the fold for the prodigal son was thus his way of cutting the long story of Anglican erring ways short. The rhetoric of his dissent is therefore but his will and his way to emphasize the artless beauty of antique simplicity.